Alternative Splicing of the SLCO1B1 Gene: An Exploratory Analysis of Isoform Diversity in Pediatric Liver - Bianca D. vanGroen; Chengpeng Bi; Roger Gaedigk; Vincent S. Staggs; Dick Tibboel; Saskia N. deWildt; J. Steven Leeder (Wiley, 2020)
The hepatic influx transporter OATP1B1 (SLCO1B1) plays an important role in the disposition of endogenous substrates and drugs prescribed to children. Alternative splicing increases the diversity of protein products from > 90% of human genes and may be triggered by developmental signals. As concentrations of several endogenous OATP1B1 substrates change during growth and development, with this exploratory study we investigated age‐dependent alternative splicing of SLCO1B1 mRNA in 97 postmortem livers (fetus‐adolescents). Twenty‐seven splice variants were detected; 10 were confirmed by additional bioinformatic analyses and verified by quantitative polymerase chain reaction, and selected for detailed analysis based on relative abundance, association with age, and overlap with an adjacent gene. Two splice variants code for reference OATP1B1 protein, and eight code for truncated proteins. The expression of eight isoforms was associated with age. We conclude that alternative splicing of SLCO1B1 occurs frequently in children; although the functional consequences remain unknown, the data raise the possibility of a regulatory role for alternative splicing in mediating developmental changes in drug disposition.